Effect of High-Speed Milling Tool Path Strategies on the Surface Roughness of Stavax ESR Mold Insert Machining - Mebrahitom, A.; Rizuan, D.; Azmir, Azhari; M., Nassif (IOP Publishing, 2016)
High speed milling is one of the recent technologies used to produce mould inserts due to the need for high surface finish. It is a faster machining process where it uses a small side step and a small down step combined with very high spindle speed and feed rate. In order to effectively use the HSM capabilities, optimizing the tool path strategies and machining parameters is an important issue. In this paper, six different tool path strategies have been investigated on the surface finish and machining time of a rectangular cavities of ESR Stavax material. CAD/CAM application of CATIA V5 machining module for pocket milling of the cavities was used for process planning.